2021
DOI: 10.34172/jcs.2021.022
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care and Its Predictive Factors in Hemodialysis Patients

Abstract: Introduction: Chronic kidney disease is a serious problem and patients need active self-care. This study focuses on the relationship between self-care and its predictive factors in hemodialysis (HD) patients. Methods: This multicenter correlational study was conducted on 201 HD patients referring to HD centers in the west of Tehran, Iran. A multi-stage sampling method was used to select the samples. Data were collected using self-care Scale, Paloutzian-Ellison Spiritual Well-Being Scale, and Connor Davidson Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(43 reference statements)
0
7
1
Order By: Relevance
“…There is a negative relationship between spiritual well-being and death anxiety. The resilient person can think positively, can easily control negative emotions, and have self-confidence 16,17 . Previous studies have reported a negative relationship of high social support with rate of incident of disease and death 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…There is a negative relationship between spiritual well-being and death anxiety. The resilient person can think positively, can easily control negative emotions, and have self-confidence 16,17 . Previous studies have reported a negative relationship of high social support with rate of incident of disease and death 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…-Set detailed goals that can be improved by week 5 -Emotional support and setting a meeting date for next week. 5 Dry weight and nutritional status assessment -Share your current situation for the past week and any inconveniences during dialysis or inconveniences in your daily life.…”
Section: Discussionmentioning
confidence: 99%
“…These engaging in regular physical activity, taking prescribed medications, and maintaining a proper diet [4]. Therefore, self-care is vital for disease management because it helps reduce chronic physical and mental disease complications [5].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…In a study on hemodialysis patients, Avanji et al stated that self-care and resilience have a negative correlation with age, so that self-care and resilience decrease with increasing age among people (Avanji et al, 2021). In explaining these results, it can be said that most anxiety disorders, such as generalized anxiety disorder, panic, and phobia, which are characterized by anxiety, are more common at a younger age and decrease with increasing age (Heidari et al, 2020); nonetheless, since Corona anxiety is caused by the disease itself, it is different from the general tension and anxiety created in the society.…”
Section: Discussionmentioning
confidence: 99%